2012
DOI: 10.1088/1674-0068/25/03/254-260
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Effects on the Photophysical Properties of 2,3-dihydro-3-keto-1H-pyrido[3,2,1-kl]phenothiazine

Abstract: Time-dependent density functional theory (TDDFT) and femtosecond transient absorption spectroscopy were used to investigate the photophysical properties of 2,3-dihydro-3-keto-1H-pyrido[3,2,1-kl]phenothiazine (PTZ4) and 3-keto-1H-pyrido[3,2,1-kl]phenothiazine (PTZ5). The calculated results obtained from TDDFT suggest that the red-shifts of the absorption spectra of these two fluorophores in methanol are due to the formation of hydrogen-bonded complexes at the ground state. Four conformers of PTZ4 were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, a detailed potential energy surface of the excited state of DCVJ was frequently reported. ,,,, It was reported that there are two kinds of twist decay paths, τ b and τ c , for excited DCVJ. , The disadvantageous application of the previous reported modes to DCVJ may be induced by the two different rotational decay paths in DCVJ. The solvents have shown important effects on the excited-state dynamics of fluorophores, but seldom people reported the solvent effects on the rotational decays of DCVJ. In addition, the ultrafast excited-state dynamics of DCVJ in different solvents was also not unambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a detailed potential energy surface of the excited state of DCVJ was frequently reported. ,,,, It was reported that there are two kinds of twist decay paths, τ b and τ c , for excited DCVJ. , The disadvantageous application of the previous reported modes to DCVJ may be induced by the two different rotational decay paths in DCVJ. The solvents have shown important effects on the excited-state dynamics of fluorophores, but seldom people reported the solvent effects on the rotational decays of DCVJ. In addition, the ultrafast excited-state dynamics of DCVJ in different solvents was also not unambiguous.…”
Section: Introductionmentioning
confidence: 99%